ESSENCE AND FEATURES OF THE MARKET FOR EDUCATIONAL SERVICES - Radjabova Gavxar Umarovna (Galaxy International Interdisciplinary Research Journal, 2023)
The article discusses approaches to defining the concept of “market of educational services”. The essence of the educational services market is determined. The structure is revealed and characteristics of the educational services market are given.